Development of a lateral ultrasound-guided approach for the proximal radial, ulnar, median and musculocutaneous (RUMM) nerve block in cats. (September 2020) - Otero, Pablo E.; Fuensalida, Santiago E.; Sánchez, Fernanda; Verdier, Natali; Tarragona, Lisa; Briganti, Angela; Portela, Diego A.
Abstract: Objective: To describe a lateral ultrasound (US)-guided approach to the radial, ulnar, median and musculocutaneous (RUMM) nerves through a single proximal in-plane insertion in cats and to determine whether one or two injection points are required to successfully stain all the target nerves. Study design: Prospective study. Animals: A total of eight client-owned healthy cats and 12 cat cadavers. Methods: In live cats, the US anatomy of the brachium, the landmarks and the site for needle accesses were determined. Then, 12 thawed feline cadavers were used to assess the spread of dye solution and nerve staining following the US-guided proximal-lateral-humeral RUMM injection using one and two injection points. Each cadaver was injected with 0.15 mL kg – 1 of a 0.25% new methylene blue solution in either a single injection aimed for the radial nerve of one limb (G1) or via two sites delivering 0.1 mL kg – 1 and 0.05 mL kg – 1 aimed for the radial and musculocutaneous nerves of the opposite limb, respectively (G2). Upon dissection, staining of the target nerves around their circumference for length of >1 cm was considered successful. Results: Sonoanatomy was consistent with anatomy upon dissection and target nerves were identified in all cadavers. Staining was 100% successful for the radial, median and ulnar nerves in both groups, and 41.7% and 100% for the musculocutaneous nerve in G1 and G2, respectively. Conclusions and clinical relevance: This novel lateral US-guided approach for the proximal RUMM nerve block allowed a good identification of the nerves and related structures, and it provided a consistent muscular structure through which the needle could be easily guided. An injection performed in two aliquots (within the caudal and cranial compartments of the neurovascular sheath) appeared to be necessary to successfully stain all the target nerves.